2019
DOI: 10.3390/cells8091079
|View full text |Cite
|
Sign up to set email alerts
|

Differential Consequences of Bmp9 Deletion on Sinusoidal Endothelial Cell Differentiation and Liver Fibrosis in 129/Ola and C57BL/6 Mice

Abstract: The aim of the present work was to address the role of BMP9 in different genetic backgrounds (C57BL/6, BALB/c, and 129/Ola) of mice deleted for Bmp9. We found that Bmp9 deletion led to premature mortality only in the 129/Ola strain. We have previously shown that Bmp9 deletion led to liver sinusoidal endothelial cells (LSEC) capillarization and liver fibrosis in the 129/Ola background. Here, we showed that this is not the case in the C57BL/6 background. Analysis of LSEC from Wild-type (WT) versus Bmp9-KO mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
(80 reference statements)
5
28
0
Order By: Relevance
“…BMP9, which is produced by hepatic stellate cells, induces the fenestration of the sinusoidal endothelial cells 145 (Figs 1 , 2 ). Deletion of Bmp9 in 129/Ola mice triggers hepatic fibrosis following sinusoidal capillarization (transformation of the fenestrated hepatic sinusoids into continuous capillaries, with synthesis of a basement membrane of collagen between the endothelial cells and the hepatocytes) 146 (Table 1 ).…”
Section: Bmp Signallingmentioning
confidence: 99%
“…BMP9, which is produced by hepatic stellate cells, induces the fenestration of the sinusoidal endothelial cells 145 (Figs 1 , 2 ). Deletion of Bmp9 in 129/Ola mice triggers hepatic fibrosis following sinusoidal capillarization (transformation of the fenestrated hepatic sinusoids into continuous capillaries, with synthesis of a basement membrane of collagen between the endothelial cells and the hepatocytes) 146 (Table 1 ).…”
Section: Bmp Signallingmentioning
confidence: 99%
“…However, their immature nature made them unable to develop fenestrae and maintain HSC quiescent [83]. Besides NO, Hedgehog (Hh) signaling has also been implicated in LSEC capillarization by regulating liver X receptor (LXR) and BMP9 among others [74][75][76][77][78][79]. Although previously suggested, studies using caveolin-1 knockout mice have demonstrated that caveolin-1 has been observed in fenestrae but it is not involved in capillarization [80,81].…”
Section: Loss Of Lsec Fenestraementioning
confidence: 99%
“…Plasma pharmacokinetic was obtained from fluorescence imaging and ICP-MS measurements after analyses through a noncompartment model (GraphPad Prism 7.00, GraphPad Software, La Jolla California USA).Noninvasive SWIR imaging on mice with vascular disorders. Generation of Bmp9-KO mice in the 129-P2/Ola-Hsd genetic background (named here for easiness 129/Ola) has been previously described9,10 . Briefly, Bmp9-KO mice in the C57BL/6 genetic background were obtained from Dr Se-Jin Lee (Johns Hopkins University, Baltimore, MD) and back-crossed for 10 generations with 129-P2/Ola-Hsd wild-type mice (Harlan France, Gannat, France).All animals experiments followed the institutional guidelines formulated by the European Community for the Use of Experimental Animals were approved by ethics committees (CEA ethic committee for animal breeding and Cometh38 for in vivo imaging) and the French Ministry of Research and Education.…”
mentioning
confidence: 99%